2012
DOI: 10.3807/josk.2012.16.4.349
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of a GaN Light-emitting Diode (LED) with a Centered Island Cathode

Abstract: Uniform spreading of injection current in light-emitting diodes (LEDs) is one of the crucial requirements for better device performances. It is reported that non-uniform current spreading leads to low output power, high current crowding, heating, and reliability degradation of the LED device. This paper reports on the effects of different surface and electrode geometries in the LEDs. To increase the output power of LEDs and reduce the series resistance, a rectangular-type LED (RT-LED) with a centered island ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Also, Schubert et al and Kang et al previously reported that the self-heating could also be reduced by changing the electrode geometries. 9,20 Through our theoretical calculation, we find that longer effective n-electrode length is beneficial for the higher efficiency, too. Here, the effective n-electrode length is the part of the n-electrode length that allows for effective current spreading from the p-electrode to the n-electrode.…”
mentioning
confidence: 80%
“…Also, Schubert et al and Kang et al previously reported that the self-heating could also be reduced by changing the electrode geometries. 9,20 Through our theoretical calculation, we find that longer effective n-electrode length is beneficial for the higher efficiency, too. Here, the effective n-electrode length is the part of the n-electrode length that allows for effective current spreading from the p-electrode to the n-electrode.…”
mentioning
confidence: 80%
“…The EQE of an LED can be expressed as the product of the current injection efficiency (CIE, η inj ), internal quantum efficiency (IQE, η int ), and light extraction efficiency (LEE, η extr ) [3,4]. The LEE of an LED depends strongly on the critical angle θ c for total internal reflection at the interface between the two media, which is determined by Eq.…”
Section: Introductionmentioning
confidence: 99%